Corporate profile, human resource management and level of profitability of secondary level tutorial centers in Iloilo City - Ereña, Jerry Mar.; Espiritu, Kristin Rye.; Macalipay, Jim Paolo; Machado, Emily (2016)
Executive summary-This research study entitled "Corporate profile, Human Resource management and Level of Profitability of Secondary Level Tutorial Centers in Iloilo City" provides and analysis and evaluation of current human resource management practices of the tutorial centers in Iloilo City and their corresponding effect on overall profitability. A comparative analysis of six respondent tutorial centers were done under a descriptive-explanatory research design. The respondents were identified through convenience sampling. It was conducted in a span of three months. Data were gathered through structured interview schedules addresses to the management of the centers. Answers to interview questions were analyzed to determine common practices of the tutorial centers. It was concluded that human resource management practices highly affect the level of profitability. Given the results, the researchers recommended that: a) Tutorial centers include background checks, reference checks and demonstrative teaching in screening tutors ; b) Tutorial centers with no formal training programs should require applicants to ave at least three continuous months of meaningful teaching experience. ; c) Tutorial centers include tutorial session observations of existing tutors as part of their tutor orientation ; d) Tutorial centers conduct weekly arbitrary tutor supervision ; e) Tutorial centers conduct regula group discussions among head instructor and tutors, mainly focused on classroom management ; f) Tutorial centers conduct regular and formal tutor performance evaluation.
Research Paper (BA 199-Business Research) -- [Iloilo City : UPV-CM, 2016].